Macrophage-derived exosome promotes regulatory T cell differentiation in malignant pleural effusion - Shao, Ming-Ming; Pei, Xue-Bin; Chen, Qing-Yu; Wang, Feng; Wang, Zhen; Zhai, Kan (Frontiers in Immunology, 2023)
Tumor-associated macrophages are one of the key components of the tumor microenvironment. The immunomodulatory activity and function of macrophages in malignant pleural effusion (MPE), a special tumor metastasis microenvironment, have not been clearly defined. Methods: MPE-based single-cell RNA sequencing data was used to characterize macrophages. Subsequently, the regulatory effect of macrophages and their secreted exosomes on T cells was verified by experiments. Next, miRNA microarray was used to analyze differentially expressed miRNAs in MPE and benign pleural effusion, and data from The Cancer Genome Atlas (TCGA) was used to evaluate the correlation between miRNAs and patient survival. Results: Single-cell RNA sequencing data showed macrophages were mainly M2 polarized in MPE and had higher exosome secretion function compared with those in blood. We found that exosomes released from macrophages could promote the differentiation of naïve T cells into Treg cells in MPE. We detected differential expression miRNAs in macrophage-derived exosomes between MPE and benign pleural effusion by miRNA microarray and found that miR-4443 was significantly overexpressed in MPE exosomes. Gene functional enrichment analysis showed that the target genes of miR-4443 were involved in the regulation of protein kinase B signaling and lipid biosynthetic process. Conclusions: Taken together, these results reveal that exosomes mediate the intercellular communication between macrophages and T cells, yielding an immunosuppressive environment for MPE. miR-4443 expressed by macrophages, but not total miR-4443, might serve as a prognostic marker in patients with metastatic lung cancer.